Effect of electronic interactions and coordination spheres on ionic diffusion in LaxSr1-xGayMg1-yO3-δ. (February 2022) - Zhao, Yao; Kilner, John; Ishihara, Tatsumi; Yoshizawa, Kazunari; Staykov, Aleksandar
Abstract: The effect of the partial covalent character of cations on their ionic diffusivity in Lax Sr1-x Gay Mg1-y O3-δ, a perovskite with Ax A'x-1 By B'y-1 O3-δ general formula, is determined computationally using plane wave, periodic, pseudopotential density functional theory. The diffusion of ions is assumed to take place by a vacancy-mediated transport mechanism. Using Vineyard's transition state theory, diffusion coefficients for each ion are obtained. The results of the calculations show that at temperature of 1000 K the diffusivity of the oxide ion is greater than that of the A-site cations by at least ten orders of magnitude, and the diffusivities of the A-site cations are greater then the diffusivities of B-site cations by at least eight orders of magnitude. Those results are related to local ionic mobilities and are not representative for macroscopic ionic diffusion. The diffusivities of rather covalent, polarizable, cations (La and Ga) were found to be lower than those of more ionic, hard, cations (Sr and Mg) despite the fact that La and Ga have smaller ionic radii than Sr and Mg, respectively. The migration pathway of the B-site cations is curved for different possible locations of the necessary oxygen vacancies and the calculations revealed that the curved pathway is not caused by steric hindrance of an intervening oxide ion but rather the driving force to maximize the electronic interactions of the B cation with surrounding oxide ions along the entire migration pathway. Graphical abstract: Image 1